The Theater of Narration : From the Peripheries of History to the Main Stages of Italy - Guzzetta, Juliet (Book collections on Project MUSE., 2021)
"This is the first book in English to focus on the Theater of Narration, a genre characterized by narrators who write and perform works that revisit historical events of national importance from local perspectives"--